PENGARUH KUALITAS LAYANAN KONSUMEN TERHADAP KEPUASAN PELANGGAN DI CHATIME CEMARA MEDAN - Mora, Indo; Loi, Kesabaran (Psikologi Universitas Sari Mutiara Indonesia, 2023)
The need for food, which is a basic human need and the increasing number of Indonesian population, makes business a very popular choice in Indonesia, so that business actors increase every year. In the business world, of course, a strategy is needed that can trigger the attraction of customers, one of which is in the service sector. Service is a very influential aspect in a business that is run in order to achieve and win the competition in the business world. A company's success is influenced by aspects of service quality that are correctly handled since they can increase client satisfaction. client satisfaction is an evaluation that occurs after a purchase; if it is met, client loyalty will develop, making it crucial for the business. This study set out to objectively investigate and ascertain how customer happiness at Chatime Cemara Medan is impacted by service efficacy. The research method used in this study is a quantitative research method. The place of research was conducted in Chatime Cemara Medan. In this study, the authors distributed questionnaires with a sample size of 40 people. From the results of research conducted by the author on the impact of Chatime Cemara Medan's service performance on client satisfaction, it shows that the value of the coefficient of determination (R2) is 0.781 or 78.1% indicating the effect of service effectiveness on customer satisfaction with a sig. value of 0.000 < 0.05.